2018
DOI: 10.1007/s10695-017-0461-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris

Abstract: Spermatogenesis represents one of the most complicated morphological transformation procedures. During this process, the assembly and maintenance of the flagella and intracellular transport of membrane-bound organelles required KIF3A and KIF3B. Our main goal was to test KIF3A and KIF3B location during spermatogenesis of Boleophthalmus pectinirostris. We cloned complete cDNA of KIF3A/3B from the testis of B. pectinirostris by PCR and rapid amplification of cDNA ends (RACE). The predicted secondary and tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…26 Additionally, KIF3B is a key regulator in multiple cellular processes including mitosis, spermatogenesis, and axonal regeneration. 12,27 These cellular processes are all involved in the motor protein function of KIF3B. In this study, we found and confirmed the effect of KIF3B on the proliferation of GC cells, which is probably also due to the effect on microtubule-based material transport to achieve the regulation of cell proliferation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…26 Additionally, KIF3B is a key regulator in multiple cellular processes including mitosis, spermatogenesis, and axonal regeneration. 12,27 These cellular processes are all involved in the motor protein function of KIF3B. In this study, we found and confirmed the effect of KIF3B on the proliferation of GC cells, which is probably also due to the effect on microtubule-based material transport to achieve the regulation of cell proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…KIF3B has also been reported to be involved in the transport of membrane‐bound complexes in neurons and epithelial cells . Additionally, KIF3B is a key regulator in multiple cellular processes including mitosis, spermatogenesis, and axonal regeneration . These cellular processes are all involved in the motor protein function of KIF3B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another member of the kinesin superfamily, KIF3B, has also been found to be mutated in some cases of male infertility ( 33 ). The function of KIF3B has been studied in the context of intracellular transport and spermatogenesis in many species ( 34 36 ). A human A>T variant in OAT patients was linked to decreased KIF3B expression resulting in impaired male fertility ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mudskipper, Boleophthalmus pectinirostris (Gobiiformes, Oxudercidae) is an amphibious gobioid teleosts, which is a commercially important aquaculture species (Zhao et al 2018). It is a warm water fish that distributes in tropical mudflats along the coast of Japan, Taiwan and Southern China (Clayton 1993;Liu et al 2012).…”
mentioning
confidence: 99%